The Role of Organizational Commitment in Mediating the Influence of Work Motivation on Teacher Performance in State Vocational High Schools in Kendari City - Andilah , Sultan; Ahiri, Jafar; ., Nurwati; ., Kadir (Journal of Ecohumanism, 2024)
This research analyzes the mediating role of organizational commitment in mediating the influence of work motivation on the performance of state vocational school teachers in Kendari City. Using quantitative methods with an explanatory research approach, this study involved 196 respondents from 7 state vocational schools in Kendari City, selected through purposive sampling. The results show that work motivation positively and significantly affects organizational commitment (path coefficient 0.510, p-value 0.000) and teacher performance (path coefficient 0.486, p-value 0.000). Organizational commitment has a significant effect on teacher performance (path coefficient 0.362, p-value 0.000). Mediation analysis confirms work motivation influences teacher performance through organizational commitment (path coefficient 0.184, p-value 0.000). In conclusion, work motivation is important for increasing a teacher's organizational commitment and improving teacher performance. The Southeast Sulawesi Provincial Government, in this case the education department, is advised to carry out regular monitoring of teacher performance and the effectiveness of training programs that have been implemented. This evaluation is important to ensure that the program meets the needs of teachers and students. It is recommended that further research use longitudinal studies and be carried out by comparing the influence of work motivation in various types of schools (for example, private versus public) or comparing vocational schools versus high schools. to gain greater insight into the dynamics of motivation in the education sector.